Application of the PDEODE Learning Model Assisted by PhET Simulation to Improve the Cognitive Learning Outcomes of Physics Science for Class VIII Students - Faza, Farzana Fakhira; Nasir, Muhammad; Rahmad, M. (Journal of Educational Sciences, 2024)
Based on the results of a needs analysis conducted by researchers on class VIII students at SMP Negeri 8 Pekanbaru regarding their perceptions of science learning at school, it is known that almost all class VIII students do not understand science lessons. This is due to the use of conventional teaching methods without the help of learning media. One of the facilities that is available and can be used is PhET Simulation. This research aims to determine the cognitive learning outcomes of physics science for class VIII students through the application of the PDEODE learning model assisted by PhET Simulation. This research uses a quantitative approach using experimental methods. The population of this research was class VIII students at SMP Negeri 8 Pekanbaru. Instruments and data collection techniques include posttest. Data analysis includes descriptive analysis with a focus on average student cognitive learning outcomes, as well as inferential analysis through normality tests, homogeneity tests, and hypothesis tests. The research results show that the application of the PDEODE learning model with the support of PhET Simulation causes an increase in students' cognitive learning outcomes in physics subjects.